Netrin-1 in cancer: Potential biomarker and therapeutic target?. Issue 4 (April 2017) - Kefeli, Umut; Ucuncu Kefeli, Aysegul; Cabuk, Devrim; Isik, Ulas; Sonkaya, Alper; Acikgoz, Ozgur; Ozden, Ercan; Uygun, Kazim
Netrin-1, a laminin-related protein, is known to be involved in the nervous system development. Recently, Netrin-1's involvement in other processes such as cell adhesion, motility, proliferation, and differentiation that are important for the development of epithelial tissues has been described. In addition, Netrin-1 and its receptors, deleted in colorectal cancer and uncoordinated-5 homolog, have been linked to apoptosis and angiogenesis. Since these properties are essential for tumor development, Netrin-1 and its receptors have been reported to promote tumorigenesis in many types of cancers. Here, we review the Netrin-1 mediated regulation of cancer, its potential use as a biomarker, and the targeting of the Netrin-1 pathway to treat cancers.